(untitled) (Jurnal Kemanusiaan, 2017)
ABSTRACT This paper discusses the question of morals and ethics, particularly among graduates in implementing the mandate and responsibility is held. In addition to presenting the importance of morals and ethics in the world of work, this paper also examines the human responsibility as a caliph and its relevance to a life lived. Next, the discussion on importance of moral and ethical in generating the development of civil generation also featured. Overall, morals and ethics are among the things that need to be emphasized to produce individuals who have excellent professional level in accordance with the chosen career. ABSTRAK Makalah ini membincangkan persoalan akhlak mulia dan etika, khususnya dalam kalangan graduan dalam melaksanakan amanah dan tanggungjawab yang dipegang. Selain membentangkan kepentingan akhlak dan etika dalam dunia pekerjaan, makalah ini turut mengupas tanggungjawab manusia sebagai khalifah dan relevannya kehidupan yang dilalui. Seterusnya, perbincangan mengenai pentingnya nilai akhlak dan etika dalam menjana pembentukan generasi madani turut diketengahkan. Secara keseluruhannya, akhlak dan etika adalah antara perkara yang perlu diberikan penekanan untuk melahirkan individu yang mempunyai tahap professional yang cemerlang sesuai dengan kerjaya yang diceburi.